Pengaruh Varian Menu, Harga, dan Suasana Cafe, Terhadap Kepuasan Konsumen Cafe Miltie Garden Mulawarman Banjarmasin - Meika Marito Sihombing; Muhammad Hasanur Arifin; Maryono Maryono (Smart Business Journal, 2021)
The study aims to determine and test the effect partially and simultaneously Variant Menu (X1), Price (X2), and Cafe Atmosphere (X3) on Customer Satisfaction (Y). This study uses a quantitative approach. The number of samples was 97 people using Non-Probability Sampling technique. Data collection techniques by means of questionnaires and data analysis techniques used are Multiple Linear Analysis using SPSS 25.0. The test results show that the Menu Variant (X1) with a sig value of 0.020 with a large influence of 0.20 or 20.6% has a positive and significant effect on consumer satisfaction. Price (X2) with a sig value of 0.001 with a large influence of 0.304 or 30.4% has a negative and significant effect on customer satisfaction. Cafe atmosphere (X3) with a sig value of 0.013 with a large influence of 0.229 or 22.9% has a positive and significant effect on consumer satisfaction. Meanwhile, based on the simultaneous test (F test), it can be seen that F count in the sig = 0,000 column which shows a number less than 0.05 or 0,000<0,05 with a Determinant Coefficient Value (R2) with a large effect of 0.681 or 68.1%, while 31.9% is from other variables not examined in this study.  Keywords: Menu Variants, Prices, Cafe Atmosphere, Customer Satisfaction